How Gender Norms Affects women’s Access to Labor Markets and Entrepreneurship in Pakistan - Sidra Shaheen; Ammara Azam*; Abdullah Hammad; Saba Javed (Journal of Religion and Society, 2025)
Women’s participation in Pakistan’s labor market and entrepreneurship remains significantly constrained by entrenched gender norms, despite recent economic reforms and inclusion initiatives. These social expectations surrounding women’s modesty, family honor, and domestic responsibilities restrict their mobility and economic agency, perpetuating gendered economic disparities. The purpose of this study is to examine how gender norms affect women’s access to labor markets and entrepreneurship in Pakistan, with freedom of movement as a mediating variable and educational level as a moderating factor. A quantitative, cross-sectional design was employed using survey data from 242 women across urban and rural regions of Pakistan. Validated measurement scales assessed gender norms, mobility, education, labor market access, and entrepreneurial participation. Data were analyzed through SPSS and AMOS using correlation, Model Fit, reliability, validity, mediation, and moderation analyses. Results revealed that restrictive gender norms have significant negative effects on women’s access to both labor markets and entrepreneurship. Freedom of movement partially mediated these relationships, indicating that mobility limitations serve as a key mechanism translating social norms into economic exclusion. Furthermore, education moderated the relationship between gender norms and mobility, demonstrating that higher educational attainment mitigates the restrictive effects of traditional norms. These findings underscore that structural and cultural barriers must be addressed concurrently. Policy implications include integrating mobility-enhancing and norm-change interventions with educational initiatives to foster women’s economic inclusion. The study advances gender and development theory through an integrated mediated-moderated model, offering a framework for designing holistic, context-sensitive empowerment policies. Keywords: Gender norms; Freedom of movement; Women’s economic empowerment; Labor market access; Entrepreneurship; Education